Social Construction Theory of Reality: A Case Study of Anti Anorexia Campaign Poster - Darisman, Aris; Hilman, Doddy; Homan, Devi Kurniawati (Bina Nusantara University, 2016)
Although Constructivism Theory of reality is categorized as a Subjective Theory, in terms of the construction process, it also had an objective feel. This could be observed in the three forms of realities that became the entry concept, namely: Objective Reality, Symbolic Reality, and Subjective Reality. The aim of this study was to analyze and understand a cultural tendency today's society through the lens of a philosophical. The philosophical theory of culture which had been regarded as something far beyond the reach became clear glasses in a tendency to see and understand the socio-cultural community. This research told about the dangerous of socio-culture community that could affect someone?s life. In this case was people who suffer anorexia and bulimia. This phenomenon could be avoided by doing campaign and some advertisement about the danger of this disease. The research method was assessing visual data in the form of a social campaign poster, study or library research, strengthened with the supporting theoretical basis study. In this research, the data obtained from photo documentation, literature study through books and scientific studies regarding social issues related to the theme. This research finds out that society, in general, is associated with the philosophical and socio-cultural studies. It is expected to occur a parallel relationship between disciplines (social, cultural, philosophical) and practices that occur in people's daily behavior.